Regulation of Syk activity by antiviral adaptor MAVS in FcεRI signaling pathway - Kawakami, Yuko; Kimura, Miho; Widjaja, Christella; Kasakura, Kazumi; Ando, Tomoaki; Kawakami, Yu; Obar, Joshua J.; Kawakami, Toshiaki (Frontiers in Allergy, 2023)
Background: Mast cells are the major effector cell type for IgE-mediated allergic reactions. Recent studies revealed a role for mast cells in orchestrating the host response to viral infections. Objective: We studied the relationship between FcRI (high-affinity IgE receptor) and RIG-I-like receptor (RLR)-mediated antiviral signaling pathways. Methods: Mast cells (BMMCs) were cultured from bone marrow cells from mice deficient in MAVS or other RLR signaling molecules. MAVS expression was restored by retroviral transduction of MAVS-deficient BMMCs. These cells were stimulated with IgE and antigen and their activation (degranulation and cytokine production/secretion) was quantified. FcRI-mediated signaling events such as protein phosphorylation and Ca2+ flux were analyzed by western blotting and enzyme assays. WT and mutant mice as well as mast cell-deficient KitW-sh/W-sh mice engrafted with BMMCs were subjected to passive cutaneous anaphylaxis. Results: Unexpectedly, we found that mast cells devoid of the adaptor molecule MAVS exhibit dramatically increased cytokine production upon FcRI stimulation, despite near-normal degranulation. Consistent with these observations, MAVS inhibited tyrosine phosphorylation, thus catalytic activity of Syk kinase, the key signaling molecule for FcRI-mediated mast cell activation. By contrast, mast cells deficient in RIG-I, MDA5 or IRF3, which are antiviral receptor and signaling molecules upstream or downstream of MAVS, exhibited reduced or normal mast cell activation. MAVS-deficient mice showed enhanced late-phase responses in passive cutaneous anaphylaxis. Conclusion: This study demonstrates that the adaptor MAVS in the RLR innate immune pathway uniquely intersects with the adaptive immune FcRI signaling pathway.